Voices from the underworld : Chinese hell deity worship in contemporary Singapore and Malaysia - Graham, Fabian (Alternative sinology., 2020)
Voices from the Underworld' focuses on Singapore and Malaysia's contemporary Chinese Underworld traditions where Hell deities are now amongst the most commonly venerated deities on altars and when channelled through spirit mediums. Intended for academics, lecturers, students, and those intrigued with Chinese culture, while highlighting the Taoist and Buddhist cosmologies upon which present-day beliefs and practices are based, the ethnography provides readers with unique insights into the lived tradition.0Embracing ontological and dialogic approaches to religious phenomena, alterity is taken seriously, and practitioner's beliefs interpreted without bias. The emic voice is literally heard through first-person dialogues between the author and channelled Underworld deities throughout the ethnography. This alternative approach challenges wider present-day discourse concerning the interrelationships between sociocultural and spiritual worlds.